Factors associated with failure of intermittent nebulization with short-acting beta-agonists in children with severe asthma exacerbation - Prapasri Kulalert (2020)
© 2020 Kulalert et al. Purpose: Intermittent nebulization of short-acting beta-agonists (SABA) is the initial treatment of choice for children with asthma exacerbation. However, children with severe asthma exacerbation (SAE) may not show an adequate response and need aggressive stepwise therapy. We aimed to explore factors associated with a poor response to intermittent nebulized SABA in children with SAE. Methods: A retrospective cohort study of children with SAE diagnosed according to the definition of the British Guidelines on the Management of Asthma, who were admitted at Hat Yai Hospital from January 1, 2015, to December 31, 2017. All children were treated with intermittent SABA nebulization. Treatment failure was defined as children needing escalated therapy. Logistic regression with confounding score adjustment was used to explore the predictors of treatment failure. Results: One hundred thirty-three children were included in the analysis, 59 were in the failure group and 74 were in the success group. After adjusting for potential confounders, they were significantly associated with a previous history of intubation (adjusted OR 6.46, 95% CI 1.13 to 36.79, p=0.036), receiving <3 doses of nebulized salbutamol in the emergency room (ER, aOR 3.21, 95% CI 1.15 to 9.02, p=0.027), ER measured oxygen saturation (SpO2) <92% (adjusted OR 3.02, 95% CI 1.18 to 7.75, p=0.022), and exacerbation triggered by pneumonia (adjusted OR 2.67, 95% CI 1.19 to 6.00, p=0.017). Conclusion: We identified four prognostic factors of treatment failure in children with SAE: a previous history of intubation; receiving <3 doses of nebulized salbutamol in the ER, SpO2 at ER <92%; and exacerbation triggered by pneumonia. Further prospective studies are required to confirm our findings before clinical implementation.